Memo from Butcher (1966)
A memo dated May 11 from the Committee to Re-Elect Governor Brown, sent by Butcher to several staff members regarding Bernie Elias. It instructs recipients that after each event, they must submit a summary of press coverage to the press department. Specifically, they are asked to report which TV stations, radio stations, and newspapers covered each event.